Evaluation of the revised New Zealand national newborn screening protocol for congenital hypothyroidism. (21st October 2016) - Heather, Natasha L.; Hofman, Paul L.; de Hora, Mark; Carll, Joan; Derraik, José G.B.; Webster, Dianne
Summary: Objective: The aim of this study was to assess the performance of the revised New Zealand (NZ) newborn screening TSH cut‐offs for congenital hypothyroidism (CHT). Methods: Screening data over 24 months were obtained from the NZ newborn metabolic screening programme, which utilizes a 2‐tier system of direct clinical referral for infants with markedly elevated TSH, and second samples from those with mild TSH elevation. We evaluated the impact of a reduced TSH threshold (50 to 30 mIU/l blood) for direct notification and a lower cut‐off (15 to 8 mIU/l blood) applied to second samples and babies older than 14 days. Results: In 2013 and 2014, 117 528 infants underwent newborn screening for CHT. Fifty‐two CHT cases were identified by screening (47 general newborn population, five repeat testing in low‐birth‐weight infants) and one case was missed. Thirty‐two infants with screening TSH ≥30 mIU/l were directly referred at a median of 9 days (5–14) and 15 with TSH 15–29 mIU/l were referred after a second sample at a median of 20 days (9–52, P < 0·001). All directly referred infants were confirmed as CHT cases with no earlier referrals as a result of the reduced threshold. The lower TSH cut‐off applied to second samples lead to the identification of six extra cases of CHT (15% increase) from seven extra clinical referrals. Conclusions: The NZ screening programme achieved a 15% increase in CHT case detection for minimal increase in workload or anxiety for families of healthy infants. A further decrease in the threshold for direct referral may allow earlier diagnoses.